Phenology of the endangered palm Ceroxylon quindiuense (Arecaceae) along an altitudinal gradient in Colombia - Martínez, Blanca (2021)
Introduction: Understanding the phenology of plant populations is vital for their conservation and management. We studied the vegetative and reproductive phenology of the endangered palm Ceroxylon quindiuense along an altitudinal gradient in the Central Cordillera of Colombia. Objective: We describe the leaf production rate, and flowering and fruiting cycles, and calculate food offer for the fauna, as a tool for the proper management of the palm. Methods: At each sampling site (2 400, 2 600, 2 800, 3 000 m.a.s.l.), we marked 40 adult individuals (20 pistillate, 20 staminate), which we followed bimonthly for 24 months. We studied leaf production by counting fallen leaves. We followed flower and fruit production through observations with binoculars and photographs. Results: Each adult individual produced, on average, one leaf every 61 days. Although isolated individuals flowered throughout the year, most palms flowered synchronously at each elevation in October 2016-August 2017 and in August 2018-February 2019 and had ripe fruits 7-13 months later. Flowering started at 2 600 m, followed by 2 800 and 3 000 m. Palms at 2 400 m, the lower limit of the palm stands in the area, showed a singular behavior, with scarce flower and fruit production, some individuals that changed sex, and a higher proportion of pistillate palms. Each palm produced 1-11 (x̄ = 5.3, SD = 2.2) inflorescences and 1-10 (x̄ = 5.3, SD = 2.2) infructescences. The average number of fruits per infructescence was 4 465 (SD = 1 488). With an estimated population of adult palms between 256 000 and 600 000 and an overall ratio of pistillate: staminate individuals 1:1 or 1:2, total fruit production in the area during each fruiting period is estimated as 2.0-7.1 billion fruits. Conclusions: The huge number of flowers and fruits and their gradual availability along the altitudinal gradient have a major impact on the spatial and temporal distribution of food offer for fauna associated with the palm.